Engineering circular bacteriocins: structural and functional effects of α-helix exchanges and disulfide introductions in circularin A - Liu, Fangfang; van Heel, Auke J.; Kuipers, Oscar P. (Frontiers in Microbiology, 2024)
Circular bacteriocins form a distinct group of antimicrobial peptides (AMPs) characterized by their unique head-to-tail ligated circular structure and functional properties. They belong to the ribosomally synthesized and post-translationally modified peptide (RiPP) family. The ribosomal origin of these peptides facilitates rapid diversification through mutations in the precursor genes combined with specific modification enzymes. In this study, we primarily explored the bacteriocin engineering potential of circularin A, a circular bacteriocin produced by Clostridium beijerinckii ATCC 25752. Specifically, we employed strategies involving αhelix replacements and disulfide bond introductions to investigate their effects on both biosynthesis and bioactivity of the bacteriocin. The results show the feasibility of peptide engineering to introduce certain structural properties into circularin A through carefully designed approaches. The introduction of cysteines for potential disulfide bonds resulted in a substantial reduction in bacteriocin biosynthesis and/or bioactivity, indicating the importance of maintaining dynamic flexibility of α-helices in circularin A, while reduction of the potential disulfide in one case increased the activity. The 5 α-helices of circularin A were respectively replaced by corresponding helices from another circular peptide, enterocin AS-48, and modestly active peptides were obtained in a few cases. Overall, this study provides valuable insights into the engineering potential of circular bacteriocins as antimicrobial agents, including their structural and functional restrictions and their suitability as peptide engineering scaffolds. This helps to pave the way for the development of novel antimicrobial peptides with tailored properties based on circular bacteriocins.